Analisis Terhadap Penyelesaian Tindak Pidana Kasus Pencurian - Nur Suryani Siwi (PSHPM Untag Semarang, 2025)
The high unemployment rate in Indonesia has caused more people to experience economic conditions around the poverty line. This has subsequently led to a tendency for crime in Indonesia to increase. The most common crime committed is theft. The motive for theft is largely economic pressure. Theft is not considered a serious crime, but it can still be subject to criminal law. Theft can be divided into two types: petty theft and ordinary theft. There are several differences between the two, although the boundaries must be considered. This study analyzes how judges adjudicate theft cases. Judges need to pay attention to several factors related to elements that aggravate the defendant's theft. In this study, the research method used is descriptive-analytical and analyzed based on secondary and primary data